Strategi Meningkatkan Literasi Membaca Siswa Sekolah Dasar Melalui Pengadaan Pojok Baca di Kelas - Santuni, Bela; Dalem, Kadek Bisma Taruna; Murtini, Kadek Dwi; Putra, I Putu Pur Adi; Juliwantara, Gede; Werang, Basillius Redan (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to increase the reading literacy of elementary school students by providing a reading corner in the classroom at SD Negeri 1 Banjar Tegal, Buleleng. Using qualitative research methods, data was collected from primary and secondary data sources. Primary data sources include direct classroom observations and in-depth interviews with teachers and students, while secondary data sources are obtained from analysis of documents related to literacy programs and school policies. Data collection techniques include observation, interviews and document study. Data analysis was carried out using a qualitative descriptive approach, through the stages of data reduction, data presentation and drawing conclusions. The research results showed that providing a reading corner equipped with varied and interesting books significantly increased students' interest and reading ability. Teachers who actively direct and motivate students to use the reading corner also make a positive contribution. The conclusion of this research is that reading corners are effective in creating a supportive reading environment, and collaboration between schools, teachers, and parents is critical to the success of this program. These findings can be a reference for other schools in implementing similar strategies to improve students' reading literacy.